2015
DOI: 10.1108/jidob-08-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Screening and diagnostic assessment of neurodevelopmental disorders in a male prison

Abstract: Purpose The aim of the study was to identify neurodevelopmental disorders and difficulties (NDD) in a male prison. The study used standardised tools to carry out screening and diagnostic assessment of the attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and intellectual disability (ID).Method The adult ADHD self-report scale (ASRS), 20-item Autism Quotient (AQ-20) and the Learning Disability Screening Questionnaire (LDSQ) were used to screen 240 male prisoners.Prisoners who sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Studies were inconsistent and sometimes unclear in reporting demographics and co-occurring conditions of the whole sample and the identified autistic subsample, making comparison of participant characteristics across studies difficult. Most studies involved male-majority ( n = 9, >60% male) or equal-gender ( n = 5) whole samples ( n = 4 not stated), with one study using a male-only sample (McCarthy et al, 2015). The identified autistic subsample tended to be male-majority ( n = 16, n = 2 not stated).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were inconsistent and sometimes unclear in reporting demographics and co-occurring conditions of the whole sample and the identified autistic subsample, making comparison of participant characteristics across studies difficult. Most studies involved male-majority ( n = 9, >60% male) or equal-gender ( n = 5) whole samples ( n = 4 not stated), with one study using a male-only sample (McCarthy et al, 2015). The identified autistic subsample tended to be male-majority ( n = 16, n = 2 not stated).…”
Section: Resultsmentioning
confidence: 99%
“…Autism prevalence is elevated in several other populations, though studies investigating these groups tended to have smaller sample sizes and lower quality scores as a result. Studies of prisoners estimated autism prevalence to be 3%–5% (Enayati et al, 2008; McCarthy et al, 2015), with higher prevalence in male arsonists (Enayati et al, 2008). Pinto-Martin et al (2011) reported a 5% autism prevalence in a cohort of young adults with low birth weight.…”
Section: Resultsmentioning
confidence: 99%
“…The screening tool has been applied in several studies in GB during the last few years [12]- [14] with adequate validity in contrast to findings from the present study. The usefulness of the LDSQ in a Norwegian setting does not seem to be as good, and is thus not recommended until after it has been examined further.…”
Section: Discussionmentioning
confidence: 81%
“…The LDSQ was specifically designed to be used this way, without the need for a specific professional qualification, background or training. One of the suggested reasons for delayed identification of many people with an intellectual disability is that diagnosis requires assessment by specialist staff (McCarthy et al, ), specifically by an appropriately qualified applied psychologist (British Psychological Society, ). In addition, the diagnostic process can be time‐consuming (Winters, Collett, & Myers, ).…”
Section: Discussionmentioning
confidence: 99%